The effect of a fat replacer on the physical, chemical, microbiological and sensory characteristics of blesbok (Damaliscus pygargus phillipsi) cabanossi - Mitchell, Cecil Starr (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.